Long-Term Investing. Issue 4 (1st July 2016) - Treynor, Jack L.
Abstract : We are reprinting this article by Jack Treynor, which first appeared in theMay/June 1976 issue, as a companion toStephen J. Brown's Editor's Corner about Treynor's legacy. Treynor distinguishes between ideas whose implications are obvious and consequently travel quickly and ideas that require reflection, judgment, and special expertise for their evaluation and consequently travel slowly. According to Treynor, the second kind of idea is the only meaningful basis for "long-term investing." Abstract : Reprinted from Financial Analysts Journal, vol. 32, no. 3 (May/June 1976): 56–59.